Factors Affecting the Individual Interest of Secondary School Students in Natural Science Lessons - Castro, Raúl Alberto Garcia; Chura-Quispe, Gilber; Marreros, Javier Lozano; Llapa Medina, Martín Pedro; Ramos, Luis Alberto Espinoza (Migration Letters, 2023)
Individual interest in learning natural sciences is a complex process influenced by multiple internal and external factors. The research reflects the need to determine the factors that affect individual interest in learning natural sciences in secondary school students. Two duly validated questionnaires were used, one of 18 factors that records the students’ perceptual assessments and the other that measures individual interest. The questionnaires were applied to 741 students in the 3rd, 4th and 5th grades of secondary education. By means of a backward stepwise binary logistic regression, a significant model was found that explains 55.4% of the individual interest in learning natural sciences. Family problems is the factor with the highest importance (55 %), followed by study techniques (47.9 %), didactic material (47.3 %), selective attention (42 %), teaching methods and techniques (41 %), family assessment (41 %), scientific language (32.9 %), academic self-concept (31.8 %), peer bullying (26.5 %), study habits (26.4 %) and Chat in social networks (25.4 %). It is concluded that the model is composed of a broad set (11) of internal and external factors, provides a valid conceptual framework as empirical support to explain individual interest in learning the natural sciences.